2017
DOI: 10.1111/jav.01124
|View full text |Cite
|
Sign up to set email alerts
|

Population differentiation in whiskered auklets Aethia pygmaea: do diurnal and nocturnal colonies differ in genetics, morphometry and acoustics?

Abstract: Despite a great number of empirical studies, the mechanisms of population differentiation and the factors that influence this process, particularly in seabirds, remain insufficiently understood. Here we analyzed population structure in the whiskered auklet Aethia pygmaea, a previously poorly studied alcid species with unusual differentiation in colony attendance rhythms (i.e. diurnal in the Sea of Okhotsk vs nocturnal in the Bering Sea), and examined the influence of it on intraspecific differentiation. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
1
4
0
1
Order By: Relevance
“…Additionally, all recorded Aleutian sightings of Whiskered Auklets at sea have been concentrated close to land and near known or suspected breeding sites Williams 1993, Piatt andDrew 2015). A rangewide pattern of residence near breeding colonies without long-distance movement (leading to a lack of mixing among populations) would be consistent with the high levels of genetic divergence in Whiskered Auklets recently described by Pshenichnikova et al (2017). Nevertheless, some variability in movement activity across the species' breeding range is expected because breeding islands in the Okhotsk Sea (Iony Island and Penzhina Bay; Figure 1) are surrounded by heavy pack ice cover in winter (Nihashi et al 2009).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Additionally, all recorded Aleutian sightings of Whiskered Auklets at sea have been concentrated close to land and near known or suspected breeding sites Williams 1993, Piatt andDrew 2015). A rangewide pattern of residence near breeding colonies without long-distance movement (leading to a lack of mixing among populations) would be consistent with the high levels of genetic divergence in Whiskered Auklets recently described by Pshenichnikova et al (2017). Nevertheless, some variability in movement activity across the species' breeding range is expected because breeding islands in the Okhotsk Sea (Iony Island and Penzhina Bay; Figure 1) are surrounded by heavy pack ice cover in winter (Nihashi et al 2009).…”
Section: Discussionsupporting
confidence: 77%
“…Migration to and from these sites would appear to be inevitable, although these birds could still roost on land at nearby ice-free locations such as the Kurile Islands, part of the species' breeding range (Gaston and Jones 1998; Figure 1). Okhotsk Whiskered Auklets also differ from Aleutian populations in morphology (larger body size and ornaments; Pshenichnikova et al 2017) and colony attendance (diurnal instead of nocturnal; Andreev et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…But the rhinoceros auklet nests in large colonies, is mainly neritic, and exhibits extensive genetic structuring. Those same traits are also characteristic of the whiskered auklet [111], a species that forages in tide-rips close to shore [111], and a species in which birds outfitted with geolocator tags attended the breeding colony year-round [112]. Neritic seabirds might tend to structure extensively because they conform to a one-dimensional, stepping-stone model of dispersal [105], and/or because they are unlikely to come into contact at sea with individuals from populations other than their own [79].…”
Section: Plos Onementioning
confidence: 76%
“…First, the ancient murrelet is panmictic across the North Pacific Ocean [82], and geolocator tagging revealed that some individuals crossed from the eastern into the western Pacific in the winter [81]. Second, population genetic structure exists in the whiskered auklet [111], and geolocator tagging showed that individuals in this species overwinter close to breeding colonies [112]. Third, the winter distribution of most Cassin's auklets breeding on two very large colonies in British Columbia (Triangle, Frederick islands) overlapped with that of individuals from Southeast Farallon Island in California [117,118], and the two groups are genetically homogeneous [50].…”
Section: Plos Onementioning
confidence: 99%
“…(); 64 , Pshenichnikova et al . (); 65 , Moum & Arnason (); 66 , Wojczulanis‐Jakubas et al . (); 67 , Birt et al .…”
Section: Approachunclassified